حكم إسقاط الجنين وأثره في الإرث: دراسة مقارنة بين المذاهب الأربعة والقانون الإندونسي والماليزي: The Ruling on Aborting the Fetus and Its Effect on Inheritance: A Comparative Study between the Four Sunni Schools, Indonesian Law and Malaysian Law - Andri Nirwana,; Faisal Husen Ismail ,; Dhia’ul Khaq ,; Yeti Dahliana ,; Alfiyatul Aziza ,; Ahmad Nurrohim , (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص الإجهاض ممنوع في الإسلام. يثير الإجهاض اختلافات في الرأي بين العلماء السابقين والمعاصرين حول تمكينه وتحريمه. هذا الوضع له تأثير على وراثة الأم من الطفل المجهض. لذلك ، تهدف هذه الدراسة إلى فحص آراء العلماء والقوانين في إندونيسيا وماليزيا فيما يتعلق بالإجهاض وتأثيره على ملكية الميراث. منهجية هذه الدراسة وصفية نوعياً. منهج هذا البحث وصفي للمحتوى من خلال الأدب. الكتب والمجلات ومقتطفات الصحف واللوائح القانونية هي المراجع الرئيسية لهذه الدراسة. توصلت هذه الدراسة إلى وجود أوجه تشابه واختلاف بين الشريعة الإسلامية والقوانين التي تمارس في إندونيسيا وماليزيا. من حيث أوجه التشابه ، تنص الشريعة الإسلامية والقوانين في إندونيسيا وماليزيا على حظر الإجهاض. ومع ذلك ، في ظروف معينة ، يمكن إجهاض الجنين لأسباب معينة مثل إيذاء الأم أو لأسباب الطبية. بالإضافة إلى ذلك ، وجدت هذه الدراسة اختلافات في العقوبة بالنسبة للنساء اللاتي أجهضن دون أي سبب وجيه. وهكذا تكشف هذه الدراسة عن توافق الشريعة الإسلامية مع القوانين المطبقة في إندونيسيا وماليزيا. لذلك ، تقترح هذه الدراسة إجراء دراسة أكثر تعمقًا للجهود المبذولة لمواءمة الشريعة الإسلامية الأوسع مع القوانين المطبقة في البلدان الإسلامية. Abstract Abortion is an act of killing to life which is forbidden in Islam. Abortion gives rise to differences of view among past and contemporary scholars on its enabling and prohibition. So, this study is to examine the views of scholars and laws in Indonesia and Malaysia related to abortion and its impact on inheritance ownership. This situation affects the inheritance of property to the mother from the aborted baby. The method of this study is qualitative descriptive. The approach of this research method is descriptive of content through literature. Books, journals, newspaper clippings, and legal regulations are the premier references to this study. This study finds that there are similarities and differences between sharia law and the rules applied in Indonesia and Malaysia. In terms of similarities, Islamic law and the laws in Indonesia and Malaysia provide for the prohibition of abortion. But, in certain circumstances, the fetus can be aborted for certain reasons, such as harming the mother or for medical reasons. In addition, this study found differences in punishment for women who had an abortion for no valid reason. Therefore, this study reveals the harmonization of Islamic law with the laws conducted in Indonesia and Malaysia. So, this study recommends forming a better in-depth study of efforts to harmonize the larger Islamic law to the rules regulated in Muslim countries.